Implementation of the “Bisheldig” Multimedia Educational Program to Enhance Health Standards within the Sakinah Household Group - Asep Nurhuda; Eka Mistiko Rini; Maria Floriana Ping; Ilma Rahim; Bagus Satria; Risna Nona (TEPIAN, 2025)
The Sakinah Household Group (Dasawisma Sakinah) faces challenges such as the digital divide and low health standards, with the frequent occurrence of flooding contributing to health issues. The Business, Healthy Living, and Digital (Bisheldig) program was created to address these concerns by offering education on digital technology usage and the promotion of clean and healthy living habits to vulnerable groups suffering from health-related problems. The objective of this study was to develop and assess the effectiveness of the Bisheldig program in enhancing digital literacy, focusing specifically on health behavior patterns, and improving the overall quality of life within the community. The Bisheldig program is designed using ADDIE model development, covering everything from analysis creation to evaluation. The program educates users on 10 essential health habits for households, such as childbirth assistance by healthcare professionals, exclusive breastfeeding, baby and toddler weighing, clean water usage, handwashing, sanitation practices, mosquito larvae control, daily physical activities, balanced nutrition, and maintaining a smoke-free indoor environment. Data was gathered through beta testing, revealing that the Bisheldig program significantly enhances digital literacy while promoting healthy living behaviors. This research offers insights for the development of multimedia-based health education initiatives and contributes to understanding the connection between digital literacy, public health, and information technology in improving household health outcomes.